2015
DOI: 10.1016/j.jspd.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the Lowest Level for Fusion in Adolescent Idiopathic Scoliosis—A Systematic Review and Meta-Analysis

Abstract: Although there was a trend toward increased pain in patients whose fusion extended to L4 or L5, there was no statistically significant association between the distal level of fusion and incidence of subsequent back pain, both with and without stratification according to severity of back pain. Because of the limitations of published research, the effect of fusion into the lower lumbar spine on back pain is unknown. Higher quality studies with long-term follow-up and consistent reporting of outcomes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…Patients with AIS treated with LIV from L4 or caudally had worse ODI scores than those treated with LIV from L3 or cranially, according to Lander et al ,15 who also found that these patients were more likely to need additional surgical treatment. However, despite the tendency for patients whose fusion reached the L4 or L5 level to endure greater pain, a meta-analysis revealed no statistically significant correlation between the distal fusion level and the incidence of later back pain 16. In our study, the SRS-22 pain domain and RDQ questionnaire results for the patients with AIS who underwent surgery at least 40 years prior have remained stable for the past 13 years.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Patients with AIS treated with LIV from L4 or caudally had worse ODI scores than those treated with LIV from L3 or cranially, according to Lander et al ,15 who also found that these patients were more likely to need additional surgical treatment. However, despite the tendency for patients whose fusion reached the L4 or L5 level to endure greater pain, a meta-analysis revealed no statistically significant correlation between the distal fusion level and the incidence of later back pain 16. In our study, the SRS-22 pain domain and RDQ questionnaire results for the patients with AIS who underwent surgery at least 40 years prior have remained stable for the past 13 years.…”
Section: Discussioncontrasting
confidence: 59%
“…However, despite the tendency for patients whose fusion reached the L4 or L5 level to endure greater pain, a meta-analysis revealed no statistically significant correlation between the distal fusion level and the incidence of later back pain. 16 In our study, the SRS-22 pain domain and RDQ questionnaire results for the patients with AIS who underwent surgery at least 40 years prior have remained stable for the past 13 years. However, the ODI score results deteriorated over the past 8 years.…”
Section: Discussionmentioning
confidence: 59%
“…Second, does Harrington instrumentation extending into the lumbar spine with correction by distraction and resultant lumbar flattening result in poor long-term outcomes 7,8 ? A 2015 systematic review and meta-analysis of medium-term, 20-year follow-up was unable to confirm or refute an association between lower levels of instrumentation and increasing pain or disability 9 .…”
mentioning
confidence: 99%
“…The findings presented here are in line with previous reviews investigating the pathophysiology and treatment of AIS. However, we chose a rather pragmatic approach: while other works focus on specific subsets of evidence such as anatomical abnormalities or treatments (i.e., [ 83 , 84 ]), our review prioritized the assessment methods. Thus, our results provide a clear, data-driven outlook that leaves less room for subjective inference.…”
Section: Discussionmentioning
confidence: 99%